Effects of vitamin E and selenium supplementation on blood lipid peroxidation and cortisol concentration in dairy cows undergoing omentopexy. Issue 4 (11th April 2018) - Mudron, P.; Rehage, J.
Summary: Twenty dairy cows with left abomasal displacement were used to investigate the effects of vitamin E and selenium treatment on thiobarbituric acid reactive substances (TBARS) and blood cortisol in dairy cows stressed by omentopexy. The cows were randomly divided into two groups. Ten hours before surgery 6 g of DL‐α‐tocopheryl acetate (6 mg/kg) and 67 mg of natrium selenite (0.1 mg/kg) in volume of 40 ml (Vitaselen ® ) were administered subcutaneously to 10 cows; the control animals ( n  = 10) received an equivalent volume of injectable water (40 ml). The injection of vitamin E and selenium produced a rapid rise ( p  < .05) in blood α‐tocopherol and selenium concentrations. The serum vitamin E increased several times 10 hr after vitamin E and Se injection and raised continuously to the highest average concentration 21.6 mg/L at hr 24 after the surgery. The highest selenium concentration was seen 10 hr after selenium administration with holding the increased concentrations in comparison with initial ones during the whole study. Two‐way ANOVA did not show significant treatment effect on plasma concentrations TBARS in the study. The plasma concentrations of thiobarbituric acid reactive substances reached the maximum value of 0.18 μmol/L in the control group 5 hr after the surgery. Twenty‐four hours after the surgery, the TBARS values returned to the initial ones. Serum cortisol increased in both groups after surgery. The highest cortisol concentrations were reached at 1 hr after surgery in the experimental and control group (56.7 ± 28.8 and 65.3 ± 26.1 μg/L respectively). A return to the levels similar to the initial ones was recognized 24 hr after the surgery. The ANOVA revealed a significant effect of vitamin E and selenium injection on plasma cortisol ( p  < .05). In conclusion, we have demonstrated that abdominal surgery resulted in typical stress changes with no significant effects of a single vitamin E/Se injection on blood lipid peroxidation. In addition, a weaker cortisol response to the abdominal surgery was recognized in animals treated with vitamin E and selenium.